Genetic Influences on the Development of Fibrosis in Crohn’s Disease - Verstockt, Bram; Cleynen, Isabelle (Frontiers in Medicine, 2016)
Fibrostenotic strictures are an important complication in patients with Crohn’s Disease, very often necessitating surgery. This fibrotic process develops in a genetically susceptible individual, and is influenced by an interplay with environmental, immunological and disease-related factors. A deeper understanding of the genetic factors driving this fibrostenotic process might help to unravel the pathogenesis, and ultimately lead to development of new, anti-fibrotic therapy. Here we review the genetic factors that have been associated with the development of fibrosis in patients with Crohn’s disease, as well as their potential pathophysiological mechanism(s). We also hypothesize on clinical implications if any, and future research directions.